Two‐Dimensional Semiconductors: From Materials Preparation to Electronic Applications. (19th April 2017) - Liu, Bilu; Abbas, Ahmad; Zhou, Chongwu
Abstract : Two‐dimensional (2D) materials are layered materials featuring strong in‐plane covalent bonding and weak intra‐plane bonding, which allow them to be easily cleaved into atomically thin materials, and be stable in such thin forms. Initiated by graphene, there has been increasing research interest in the past few years in studying growth, electronic and optoelectronic applications, and many other applications of 2D materials. In this review, recent achievements in the controlled preparation of monolayer and few‐layer 2D semiconductors are summarized, with an emphasis on transition metal dichalcogenides (TMDCs). General understanding for TMDC growth as well as approaches to grow large single crystalline TMDCs and wafer‐scale manufacturing of continuous TMDC films are discussed. In the second part, the focus is on applications of 2D semiconductors in electronics, where several key issues—including how to form good electrical contacts between electrodes and 2D semiconductors, charge carrier scattering mechanisms, and short‐channel effects—are discussed in detail. In the last section, the authors' perspective on the challenges and opportunities in the growth and electronic applications of 2D semiconductors is presented. Abstract : The most important concepts, scientific obstacles, and prospects of 2D material devices are reviewed. The importance of 2D material growth on device performance is discussed, as well as metal contacts, scattering mechanisms, and short channel effects in 2D‐material devices.